KAJIAN AWAL PEMBUATAN PUPUK CAIR ORGANIK DARI EFFLUENT PENGOLAHAN LANJUT LIMBAH CAIR PABRIK KELAPA SAWIT (LCPKS) SKALA PILOT - Fristyana Sosanty Lubis, Irvan, Dedy Anwar, Basril Amirza Harahap, Bambang Trisakti (Universitas Sumatera Utara, 2014)
The objective of this study is to design an organic liquid fertilizer manufacturing process from palm oil mill effluent (POME) at pilot scale. Materials used were effluent from further processing of biogas fermentation from POME and starter (mixture of molasses, yeast and effective microorganism). Variables measured were total solid (TS), volatile solid (VS), total suspended solid (TSS), volatile suspended solid (VSS), and chemical oxygen demand (COD), in addition, analysis content of liquid fertilizers was performed. The research consisted of production of starters and fermentation process. Loading rate was started from hydraulic retention time (HRT) 2,500 days and bioreactor performance was observed at HRT 100, 90 and 80 days. The results showed that COD concentration of bioreactor effluent decreased from 8,600 to 1,580 mg/l and from analysis content, liquid fertilizers are composed of nitrogen 0.14%, P2O5 0.05%, K2O 0.07%, MgO 0.01%, CaO 0.001mg/l, C-Organic 0,12%, and C/N Ratio 0.86.